Hubungan isi konten akun TikTok @vmuliana dengan kebutuhan informasi pencarian kerja followers - Salsabila Maharani Putri; Ninis Agustini Damayani; Encang Saepudin (Jurnal Informatio, 2023)
TikTok has become a widely used social media platform for entertainment and showcasing user creativity, including in the realm of job-seeking information. Given the rising unemployment rates in Indonesia, job information has become essential. This study aims to examine the relationship between the content information of the TikTok account @vmuliana and the job information needs of its followers. In this research, a correlation method was applied with a quantitative approach. The entire follower base of the TikTok account @vmuliana served as the research population, with 100 individuals selected as samples through a simple random selection method. Data collection techniques used were questionnaires and literature studies. To analyze the data, researchers utilized the Pearson Product Moment formula. From the analysis, a correlation coefficient was found between content information (variable X) and information needs (variable Y) amounting to r = 0.721, with a significance of 0.000 from 100 respondents. According to Guilford, this value indicates a high relationship. With a significance value of 0.000, it can be concluded that the content of the TikTok account @vmuliana is closely related to fulfilling the job search information needs of its followers.